Mechanisms of Progranulin Action and Regulation in Genitourinary Cancers - Tanimoto, Ryuta; Lu, Kuojung G.; Xu, Shi-Qiong; Buraschi, Simone; Belfiore, Antonino; Iozzo, Renato V.; Morrione, Andrea (Frontiers in Endocrinology, 2016)
The growth factor progranulin has emerged in recent years as a critical regulator of transformation in several cancer models, including breast cancer, glioblastomas, leukemias and hepatocellular carcinomas. Several laboratories, including ours, have also demonstrated an important role of progranulin in several genitourinary cancers, including ovarian, endometrial, cervical, prostate and bladder tumors, where progranulin acts as an autocrine growth factor thereby modulating motility and invasion of transformed cells. In this review we will focus on the mechanisms of action and regulation of progranulin signaling in genitourinary cancers with a special emphasis on prostate and bladder tumors.